2012
DOI: 10.3342/ceo.2012.5.1.34
|View full text |Cite
|
Sign up to set email alerts
|

Long-term Study of Sialodochoplasty for Preventing Submandibular Sialolithiasis Recurrence

Abstract: ObjectivesThe transoral removal of stones by sialodochoplasty has been popularized in the treatment of submandibular sialolithiasis. However, the effectiveness of sialodochoplasty is controversial, and there are no reports on the long-term outcomes of this procedure. The purpose of this study was to assess the effectiveness and long-term outcomes of sialodochoplasty in patients with submandibular sialolithiasis.MethodsWe conducted a cross-sectional study that included retrospective chart reviews and prospectiv… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
13
0
1

Year Published

2015
2015
2022
2022

Publication Types

Select...
4
2
1

Relationship

0
7

Authors

Journals

citations
Cited by 15 publications
(15 citation statements)
references
References 15 publications
1
13
0
1
Order By: Relevance
“…After removal of stones, sialodochotomy can be left without any suture, it can be closed with or without stent, or sialodochoplasty can be performed to prevent recurrence of symptoms or stone. It was reported that sialodochoplasty showed no significant effects on reducing symptom recurrence . Direct incision over the stone and leaving the duct without any suture were the preferred methods in this study.…”
Section: Discussionmentioning
confidence: 82%
See 1 more Smart Citation
“…After removal of stones, sialodochotomy can be left without any suture, it can be closed with or without stent, or sialodochoplasty can be performed to prevent recurrence of symptoms or stone. It was reported that sialodochoplasty showed no significant effects on reducing symptom recurrence . Direct incision over the stone and leaving the duct without any suture were the preferred methods in this study.…”
Section: Discussionmentioning
confidence: 82%
“…It was reported that sialodochoplasty showed no significant effects on reducing symptom recurrence. 10,11 Direct incision over the stone and leaving the duct without any suture were the preferred methods in this study. In our experience, it is believed that minimal manipulation of duct would lead to best recovery of duct function.…”
Section: Discussionmentioning
confidence: 99%
“…Sialendoscopy was used to identify any additional sialoliths, remaining stone fragments, or areas of ductal stenosis. Following sialendoscopy, Wharton's duct was not routinely stented nor was the sialolithotomy repaired …”
Section: Methodsmentioning
confidence: 99%
“…Following sialendoscopy, Wharton's duct was not routinely stented nor was the sialolithotomy repaired. 11,21,22 The English literature was reviewed for articles regarding CA, or any similar technique that used a combined sialendoscopic and transoral approach for the management of SMG stones following data collection from our cohort. The PubMed Central search was used to accomplish this portion of the study, using keywords that included: combined transoral sialolithotomy, combined approach technique, sialendoscopy, submandibular gland stone, and sialolithiasis.…”
Section: Methodsmentioning
confidence: 99%
“…Marchal & Dulguerov (25) indican que otra técnica es combinar la sialolitectomía con una sialodocoplastía o marsupialización, realizando una incisión para extraer el sialolito, y suturar los bordes del conducto en los bordes de la herida lo cual permitiría el drenaje del conducto formando un nuevo orificio que funcione como baipás (en inglés bypass) del flujo salival. Se ha reportado que este tratamiento puede evitar la recurrencia de cálculos salivales, aunque en otros se menciona que la existencia de una sialolitectomía no depende de realizar una sialodocoplastía según Park et al (30). Kopec et al (19) apuntan que también se puede colocar un catéter o estent (del inglés stent) de pequeño calibre en el conducto salival para evitar su estenosis; aunque ésta es una práctica que está descrita principalmente para el tratamiento de cálculos en el conducto de Stensen de la glándula parótida.…”
Section: Tratamientounclassified